Fluorescent advanced glycation end products in type 2 diabetes and its association with diabetes duration, hemoglobin A1c, and diabetic complications - Liu, Rui; Zhang, Mengyao; Xu, Li; Liu, Jingjin; Yang, Pingan; Li, Min; Qin, Jie (Frontiers in Nutrition, 2022)
Background Fluorescent advanced glycation end products (fAGEs) are generated through the Maillard reaction between reducing sugars and amino compounds. fAGEs accumulation in human bodies have been confirmed to be related to many chronic diseases. To date, the correlations between serum fAGEs levels and clinical parameters or carotid intima media thickness (CIMT) in patients with T2DM remain unclear. Thus, this study aimed to investigate the relationship between serum AGEs levels and clinical parameters or CIMT in patients with T2DM. Method A total of 131 patients with diabetes and 30 healthy controls were enrolled. Patients were divided into three groups according to diabetes duration, including ≤5, 5–10, and ≥10 years. Serum fAGEs, protein oxidation products, clinical parameters, and CIMT were determined. Results The result showed that levels of fAGEs and protein oxidation products increased with the increasing duration of diabetics. Pearson correlation coefficients of fAGEs versus hemoglobin A1c (HbA1c) were >0.5 in patients with diabetes duration ≥10 years. A continued increase in fAGEs might cause the increase of HbA1c, urinary albumin/creatinine ratio (UACR) and CIMT in patients with T2DM. Conclusion Our study suggested that levels of fAGEs could be considered as an indicator for duration of diabetics and carotid atherosclerosis. Diabetes duration and smoking might have a synergistic effect on the increment of fAGEs levels, as evidence by the results of correlation analysis in patients with long-duration diabetics (≥10 years) and smoking. The determination of fAGEs might be helpful to advance our knowledge on the overall risk of complications in patients with T2DM.